PROSTHETIC TREATMENT OF WOMEN WITH LOWER LIMB ABSENCE DURING PREGNANCY & THE POSTPARTUM PERIOD: A CHART REVIEW - Brittany Pousett; Donna Cumming; Clara Phillips; Fae Azhari; Crystal MacKay (Canadian Prosthetics & Orthotics Journal)
BACKGROUND: Little information is available for women with lower limb absence (LLA) and their prosthetists regarding expectations for prosthetic treatment during and after pregnancy. A main concern is prosthesis use and what adjustments may be required to sustain mobility.